(untitled) (Journal of NELTA, 2021)
Reading is generally considered as one of the essential language learning skills. Unfortunately, in most Bangladeshi government secondary schools, reading is not given its due respect. Recent research indicates that reading is as much important a skill as speaking or writing and therefore, Bangladeshi teachers need to change their mindset towards the significance of reading in classroom, to make the L2 learning a helpful experience for students. Five Bangladeshi teachers from three diﬀerent schools took part in the study. This study is aimed to see Bangladeshi teacher’s analysis of reading problems of their students and the teaching strategies they use in classrooms for teaching reading skills by using questionnaire and interviews as research tools. The research found that teachers recognise students’ reading problems and sincerely try to address these but their biggest impediment is the class size for which students are left alone with their reading diﬃculties. If this skill is not aptly addressed at this level, learning the other three language skills will be diﬃcult for the second language learners. Hence this research suggests that teachers’ analysis of the reading problems should be given importance to ensure students’ maximum L2 learning.